Effects of Jatropha curcas seed extract on reproductive functions in female Wistar rats - Ayinde, Taofeek Olanrewaju; Adetokunbo, Azeez Olaniyi; Biliaminu, Sikiru Abayomi; Ojulari, Sheriff Lekan; AbdulAzeez, MI; Faramade, Adeleke Alani; Balogun, Maruf Eyitayo; Afodun, Adam Moyosore; Liadi, Muideen Tella; Belewu, Moshood Adewale (Journal of Bangladesh Society of Physiologist, 2022)
Background: Jatropha curcas is a multipurpose plant with several industrial and medicinal importance. Its seeds contain many active compounds that are used as medicines with antiinflammatory, and antioxidant activity. Objective: The objective of this study is to evaluate the effects of extract of Jatropha curcas seed which is patronized locally in some communities as agent of preventing childbirth on reproductive functions in female Wistar rats. Methods: Twenty-four animals were randomly divided into four groups of 6 rats each. Group I was administered normal saline and served as control. Groups II, III and IV were given the seed extract orally at doses of 100mg/kg, 200mg/kg and 400mg/kg body weight respectively daily for 14days orally. The animals were euthanised and blood samples collected for oestrogen, progesterone, FSH and LH assay. Statistical analysis was done using statistical package for social sciences (SPSS). Differences in means was obtained using ANOVA test. All values reported in the study were expressed as mean ± SEM. Differences in mean was taken to be significant at P<0.05. Results: There was significant reduction (p<0.05) in levels of progesterone, LH and FSH in moderate and high doses of the extract. But estrogen level was significantly (p<0.05) decreased in both low and moderate doses, while the high dose showed significant (p<0.05) increase. Conclusion: There was alteration in reproductive hormones due to arrest of development of ovarian follicles. This gives it the propensity of exhibiting contraceptive activity. J Bngladesh Soc Physiol 2021;16(1): 104-110